MONITORING OF INTERACTION OF SECONDARY AND HIGHER SCHOOLS ON IMPROVEMENT OF PEDAGOGICAL PROFESSIONALISM: THEORETICAL ASPECT - H.B. Shtelmakh (Academy of Cognitive and Natural Sciences, 2010)
The article deals with the stages and conditions of effective organization concerning an interplay of secondary school and higher educational institution in the improvement of pedagogical professionalism.